2011
DOI: 10.2135/cropsci2011.03.0172
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variation and Patterns of Linkage Disequilibrium Associated with Introduced Genes in Spring Wheat

Abstract: Introduction of genes from outside a primary germplasm base has the potential to impact phenotypic diversity, genetic structure, and patterns of linkage disequilibrium (LD). Our goals were to monitor the introduction of key genes in a hard red spring wheat {Triticum aestivum L.) germplasm set using historical cultivars, to determine the impact of the introduced genes on phenotypic diversity in elite germplasm, and to assess the impact of selection history on LD. A superior alíele for bread making was introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…A single QTL, referred to as Qss.msub‐3BL , was identified by Cook et al (2004) as controlling about 75% of the variation for stem solidness in a winter wheat RIL population. The QTL also controls most of the variation for stem solidness in spring wheat (Kalous et al, 2011), and a QTL that maps to the same location has been shown to control most of the variation for stem solidness in durum wheat (Houshmand et al, 2007). The availability of a tightly linked molecular marker provided an opportunity to develop NIL that varied for alleles at Qss.msub‐3BL , and to conduct replicated trials at several locations in Montana, Washington, and Idaho that varied in yield potential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single QTL, referred to as Qss.msub‐3BL , was identified by Cook et al (2004) as controlling about 75% of the variation for stem solidness in a winter wheat RIL population. The QTL also controls most of the variation for stem solidness in spring wheat (Kalous et al, 2011), and a QTL that maps to the same location has been shown to control most of the variation for stem solidness in durum wheat (Houshmand et al, 2007). The availability of a tightly linked molecular marker provided an opportunity to develop NIL that varied for alleles at Qss.msub‐3BL , and to conduct replicated trials at several locations in Montana, Washington, and Idaho that varied in yield potential.…”
Section: Discussionmentioning
confidence: 99%
“…A major effect QTL at the same genomic location has been identified in durum wheat ( T. turgidum L.) (Houshmand et al, 2007). Kalous et al (2011) showed that Qss.msub‐3BL was the major contributor to variation in stem solidness for an association mapping panel of spring wheat lines. Lanning et al (2006) identified a second QTL with lesser effect on solid stems on chromosome 3D.…”
mentioning
confidence: 98%
“…Genes for semidwarf habit were introduced into hard red spring wheat grown in the Northern Great Plains in the 1960s and are currently found in most commercial cultivars (Kalous et al, 2011). Agronomic analysis of the McNeal/Thatcher RIL population in five Montana environments showed that the Rht-D1b allele from McNeal resulted in plants with shorter stature, more productive tillers, and increased yield of approximately 20%.…”
Section: Discussionmentioning
confidence: 99%
“…The glutenin subunits Dx2 + Dy12 encoded by Glu-D1 on chromosome 1D were deleterious for dough strength in several studies (Branlard and Dardevet, 1985;Lawrence et al, 1988), and have been replaced with the Dx5 + Dy10 subunits in many hard wheat cultivars selected for bread making (Kalous et al, 2011). Two classes of these proteins are present in the wheat kernel, including monomeric gliadin proteins and polymeric glutenin proteins that are joined by disulfide bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation